Study on Deposition Characteristics of the Electrostatic Sprayer for Pesticide Application in Greenhouse Tomato Crops - Zhanhong Guo; Jiajia Zhang; Lining Chen; Zhaoyang Wang; Hongbiao Wang; Xufeng Wang (Agriculture)
In densely planted solar greenhouses, tomato crops face increasing challenges with pest and disease control due to high temperature and humidity conditions. The existing spraying equipment often suffers from low mechanization and inadequate foliar deposition coverage. This study presents the design of a vertical spray bar electrostatic sprayer, which combines a multi-nozzle vertical spray bar with electrostatic spraying technology, making it suitable for greenhouse applications. In order to obtain the best working parameters of the sprayer, the coverage rate of the front and back sides of the tomato leaves was taken as the performance target. Key influencing factors, including electrostatic voltage, spray pressure, and target distance, were investigated using a multi-factor response surface methodology. Field experiments were conducted in a greenhouse environment based on the optimized parameters to validate the performance. The results indicate that: (1) The factors influencing droplet adherence on the upper surface of tomato leaves ranked in the order of target distance, spray pressure, and electrostatic voltage, while for the underside, the order was electrostatic voltage, target distance, and spray pressure. (2) Under the conditions of electrostatic voltage of 10 kV, spray pressure of 0.7 MPa, and target distance of 35 cm, the sprayer achieves the optimal operation of leaf comprehensive coverage. (3) Compared to non-electrostatic spraying, the greenhouse electrostatic sprayer significantly improved the coverage on both sides of the leaves, enhancing pesticide utilization efficiency. This novel electrostatic sprayer meets the operational requirements for greenhouse crop protection in the Xinjiang region of China.